If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h + 4 = 2h + -20 Reorder the terms: 4 + 8h = 2h + -20 Reorder the terms: 4 + 8h = -20 + 2h Solving 4 + 8h = -20 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 4 + 8h + -2h = -20 + 2h + -2h Combine like terms: 8h + -2h = 6h 4 + 6h = -20 + 2h + -2h Combine like terms: 2h + -2h = 0 4 + 6h = -20 + 0 4 + 6h = -20 Add '-4' to each side of the equation. 4 + -4 + 6h = -20 + -4 Combine like terms: 4 + -4 = 0 0 + 6h = -20 + -4 6h = -20 + -4 Combine like terms: -20 + -4 = -24 6h = -24 Divide each side by '6'. h = -4 Simplifying h = -4
| jh=5 | | 4r^2=9/16 | | 0.70x+0.45(30)=56.9 | | (35x^3-6x)/7x | | 1/2x+5=3x-4 | | 16c^2+24c+9=0 | | 18/-6= | | -125=-5(5+4x) | | .5x+5=3x-4 | | (x+2)/(x+6)=1/3 | | 8x+3(20-x)=5(20) | | -8/7r+4r=1/4r+73/4 | | 5(5m-7)+2=-83 | | 8x+3(20)=5(x+20) | | 2(8p+7)=94 | | q^2+20q+19=0 | | (21*2)/(15-8) | | 2x+40=12x | | -3m+3(5m-15)=99 | | -3(3n-4)=84 | | -3/5x=40 | | -393n-40=84 | | 7+4w=-9 | | 1/3x=27 | | x+3=-(4x+4) | | 2z+2=3z-1 | | 0.8x+7.8=3.4 | | 4=-7y+4y | | log[14](x-70)=3-log[14]x | | 3x^2+6xy-2y^3+6=0 | | 5=-8y+5y | | 3(k-3)=15 |